THE EFFECT OF DIGITAL TRANSFORMATION ON BUSINESS PERFORMANCE IN DENPASAR MSMEs (CASE STUDY ON GO-FOOD MERCHANT DENPASAR) - A.A. Ngurah Bagus Aristayudha; Vitalia Fina Carla Rettobjaan (Jurnal Ekonomi, 2022)
MSMEs play an important role in Indonesia, which is a country with MSMEs accounting for 60 percent of the gross domestic product, and able to provide 97 percent of the total national workforce. This shows that MSMEs play a major role in economic development in Indonesia at IDF 2019. The key to economic development through MSMEs is collaboration or partnership. Gojek Indonesia through the Go-food service is here to help MSMEs, not only marketing services for culinary products, but financial services with Gopay, delivery services with Gojek, digital operational services in terms of recording with Gobiz. Therefore, it is important to know the impact of digital transformation on MSMEs, especially in partnership with Go-food. Knowledge of this impact will be very useful for Go-food companies to develop the competitiveness of Go-food partners, especially in Denpasar. The purpose of this study was to determine the effect of digital transformation on business performance of SMEs in Denpasar. The research method used is quantitative and qualitative, namely by using a questionnaire and in-depth interviews with research respondents.